1999
DOI: 10.1007/s004310051121
|View full text |Cite
|
Sign up to set email alerts
|

In vitro immunoglobulin response of fetal B-cells is influenced by perinatal infections and antibiotic treatment: a study in preterm infants

Abstract: The results indicate that perinatal infections and administration of antibiotics depress immunoglobulin secretion in cell cultures. We suggest that in vivo B-cell activity in infected preterm infants, and infants prophylactically receiving antibiotics, could also be depressed and result in decreased immunoglobulin production in these infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…439 Premature neonates with perinatal infection or nosocomial infection may show signs of humoral immunoparalysis, manifested by decreased IgM/IgG production ex vivo as compared with production in their healthy age-matched counterparts. 440 Sepsis in early life did not reduce serum antibody titers in preterm infants after heptavalent pneumococcal conjugate vaccine exposure but was associated with a reduced opsonization titer to a single serotype, suggesting the capacity to respond to vaccination or other immune challenge may be altered. 441 In the setting of reduced classic adaptive immune function seen in early life as compared with the function in adults, innate lymphoid populations (which lack B cell receptor and T cell receptor) may play a significant role in protecting the neonate from infectious challenge.…”
Section: Innate Immune Cellular Contributionsmentioning
confidence: 88%
“…439 Premature neonates with perinatal infection or nosocomial infection may show signs of humoral immunoparalysis, manifested by decreased IgM/IgG production ex vivo as compared with production in their healthy age-matched counterparts. 440 Sepsis in early life did not reduce serum antibody titers in preterm infants after heptavalent pneumococcal conjugate vaccine exposure but was associated with a reduced opsonization titer to a single serotype, suggesting the capacity to respond to vaccination or other immune challenge may be altered. 441 In the setting of reduced classic adaptive immune function seen in early life as compared with the function in adults, innate lymphoid populations (which lack B cell receptor and T cell receptor) may play a significant role in protecting the neonate from infectious challenge.…”
Section: Innate Immune Cellular Contributionsmentioning
confidence: 88%
“…Determination of the concentration of Ig. The concentration of total Ig of IgA and IgM isotypes was determined by the sandwich ELISA method as previously described [15] using isotype specific polyclonal Ab (Sevac). Newborn plasma was used in a twofold dilution starting with 1 : 25.…”
Section: Methodsmentioning
confidence: 99%
“…As well as causing detrimental effects at the intestinal level, antibiotherapies may have an impact at the peripheral level. Recent study has shown that B-cell activity measured in ×itro is depressed in infants receiving antibiotic treatments (187).…”
Section: Discussionmentioning
confidence: 99%